Penyuluhan Pengisian dan Pelaporan SPT PPh Tahunan Wajib Pajak Orang Pribadi Bagi Guru SMP IT Daarul Istiqlal Marindal-I - Jayusman, Sri Fitria; Munawaroh, Munawaroh; Hasibuan, Melisa Zuriani; Munawaroh, Wilda Sri; Harahap, Rasyid Yudha (Maslahah: Jurnal Pengabdian Masyarakat, 2024)
Based on the PKM team survey, the problem at SMP IT Daarul Istiqlal Marindal I is that teachers' knowledge and understanding of taxation is still low. The problem continued when an interview with one of the teachers named "Ningsih" said that they were not very good at personal taxation, they did not know what SPT was and how to calculate the tax owed. There is no concern about how to carry out personal tax obligations. The problems faced by these teachers encouraged the service team to help in the form of counseling on filling out SPT and reporting consistently as the role of good citizens. Based on the PKM-PM team survey, the problems that exist at Daarul Istiqlal IT Middle School are: Lack of counseling regarding filling out annual tax returns, lack of government or other parties to become pioneers, lack of knowledge from both print and electronic media regarding procedures for filling out and reporting SPT. Annually, Lack of facilities that support increased education on the contents of the Annual SPT. The solution offered is the aspect of improving performance management. The solution that will be offered is to provide intensive assistance to partners by focusing on improving partners' skills in carrying out the learning process and can become a model school for other schools. From the results of the questionnaire, it was found that Daarul Istiqlal IT Middle School service participants' interest in practicing this service activity had been successful. Around 80% of the entire community participated and felt happy to take part in this training because it could increase their insight into tax aspects. Partners really contribute to the smooth running of community service activities.